State policies towards religion and the Russian Orthodox Church in China. Issue 1 (2nd January 2017) - Lukin, Alexander
ABSTRACT: This article examines the history and current state of the Russian Orthodox Church (ROC) in China. It analyses both the declared and actual approach of the Chinese authorities towards Orthodox believers in China, as well as the attitude taken towards that approach by the authorities in Russia, where the 'Orthodox factor' plays an increasingly prominent role in domestic and foreign policy. The author shows that Russia's most senior political leaders assist the ROC to strengthen the status of the Chinese Autonomous Orthodox Church (CAOC) and create better conditions for Chinese Orthodox believers. That effort has elevated the 'Orthodox question' to become an important issue of bilateral relations. As a result, and despite a lack of enthusiasm from the Chinese side, conditions could be created in the coming years for the normal functioning of the CAOC. At the same time, the Chinese Government is likely to consider it not as an autonomous part of the ROC (as the Orthodox canon considers it) but as one of the 'patriotic religious organisations' registered first at the provincial, and possibly later at the national level.